Effect of anion size and nano fumed silica on structural, thermal and electrical properties of chitosan polymer electrolytes / Shanti Navaratnam - Navaratnam, Shanti (2011)
Chitosan has drawn attention as a potential polymer host for polymer electrolytes due to its promising properties. In the present study, an attempt has been made to determine the role of the different anions, namely, CH3COO− and CF3SO3 −, on the ionic conductivity of chitosan-based polymer electrolyte. The effect of filler on the sample with the highest conducting anion sample was also investigated. Many research studies on polymer electrolytes have shown that the dielectric values at high frequencies and electric modulus at low frequencies are constant. In this study, it has been further investigated to validate such findings. Chitosan-based polymer electrolytes comprising ethylene carbonate and propylene carbonate (1:1) as a plasticizer and a lithium salt LiX (X = CH3COO− and CF3SO3 −) were prepared by solvent cast technique. Conductivity studies showed both systems obeyed Arrhenius behaviour and the ionic conductivity values obtained were 6.18 x 10-7 S cm-1 for the system with acetate anion and 5.01 x 10-6 S cm-1 for the system with triflate ion. It could be understood that the type of anion influences the ionic conductivity. Nano size fumed silica was added to the system with triflate ion to enhance the ionic conductivity. The highest room temperature conductivity value 5.41 x 10-5 S cm-1 was obtained by the composite electrolyte system with 2 wt. % silica. The improvement in the conductivity has also been supported by differential scanning calorimetry (DSC), X-ray diffraction (XRD) and Fourier transform infrared-spectroscopy (FTIR) studies. From DSC studies it is observed the glass transition temperature Tg decreased from 197oC to 166oC on addition of 2 wt. % silica. Lower Tg means greater polymer segmental motion and this implies faster ion conduction. XRD studies and FTIR showed the sample had lowest degree of crystallinity and highest number of free ions respectively. Dielectric behaviour of the prepared systems showed strong dependence on frequency and temperature. The prepared materials are ionic conductors.